Experimental Color Observation and Modelling of Drying Wasabi Leaves with Gas Heater in a Rack Dryer - Didik Iswadi; Ahmad Wibisana (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This study analyzed the drying characteristics of Wasabi leaves in rack dryers with gas heating at various temperatures to obtain the most suitable thin-layer drying model while evaluating the color change and mass transfer parameters. Drying was carried out for 7.5 hours at temperatures of 60, 80, 100, and 120°C with the main variables of moisture content, moisture ratio, energy consumption, effective diffusivity, and CIE Lab* and ?E color parameters. The drying curve data were analyzed using three thin layer models (Newton, Henderson and Pabis, and Page) and evaluated with coefficients of determination (R²), chi-square (X²), and root mean square error (RMSE). The results showed that the increase in drying temperature increased specific energy consumption (9.07 × 10³ – 1.91 × 10? kJ kg?¹ water) and effective diffusivity (2.49 × 10?? – 4.11 × 10?? m² s?¹), and accelerated the reduction of moisture content to 2.27–10% at 80–120°C. The moisture ratio is in the range of 0.02–0.98 and indicates a phase of high initial drying rate, followed by a period of decreasing rate until the weight is nearly constant around 240 minutes. The discoloration during drying was characterized by a decrease in L (13.91–42.69), an increase in a (?6.4 to 0.31), a decrease in b (11.93–24.78), and an increase in ?E (2.12–16.44), indicating a degradation of green pigment and a tendency to brown at high temperatures. Based on the R², X², and RMSE criteria, the Newton model at 60°C provides the best fit between the predictions and the experimental data, so it was chosen as the most representative model for describing the drying kinetics of Wasabi leaves in a gas rack dryer. These findings provide a quantitative database of energy, diffusivity, and colour change that can be used to optimise wasabi leaf drying operations for use as a raw material for natural dyes, thereby improving energy efficiency. Contribution to Sustainable Development Goals (SDGs): SDG 7: Affordable and Clean Energy, SDG 12: Responsible Consumption and Production; SDG 9: Industry, Innovation and Infrastructure.